(untitled) (REVISTA NODO, 2008)
This article is a summary of the research project «Use of Barranquilla´s Native Vegetation according to its Comfort Index», in which we analyze the environmental conditions created under the trees and, based on that, we came up with a comfort index that should be helpful for urban and architectural design, when selecting the species most likely to be used as a spatial component, given their climatic comfort potential.